Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3934/gf.2022012
|View full text |Cite
|
Sign up to set email alerts
|

A wave of green start-ups in India—The study of green finance as a support system for sustainable entrepreneurship

Abstract: <abstract> <p>Development of the economy cannot be done at the cost of deterioration of ecology. Green finance is the most practical way of economic development and ecological development. To tackle the urgent challenges of climate change, several summits and conferences have adopted a sustainable development framework for their action plans. The 2030 Sustainable Development Goals (SDGs) are a unique collection of seventeen time-bound goals that strive to balance the three sustainability objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Implementing effective communication techniques and policy interventions can enhance the influence of awareness and perception on the direction of financial resources towards sustainable projects [26]. Research has shown that effectively planned climate change communication campaigns [27] and government policies (e.g., subsidies for renewable energy) can increase public knowledge and understanding, leading to increased expenditures in sustainable projects [28].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Implementing effective communication techniques and policy interventions can enhance the influence of awareness and perception on the direction of financial resources towards sustainable projects [26]. Research has shown that effectively planned climate change communication campaigns [27] and government policies (e.g., subsidies for renewable energy) can increase public knowledge and understanding, leading to increased expenditures in sustainable projects [28].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the research of related fields, scholars mostly focus on pollution permits systems (Ren et al, 2022a , b ) and corporate social responsibility disclosure (Hong et al, 2020 ), and financial resource allocation (Jia et al, 2021 ; Su et al, 2021 ; Bhatnagar et al, 2022 ; Khan et al, 2022 ), environmental regulation (Xu et al, 2022 ), financial technology (Yao et al, 2021 ), and other perspectives have studied the influencing factors of green innovation. Few scholars have paid attention to the institutional environment and green innovation capability of R&D investment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In recent years, after the introduction of the Sustainable Development Goals (SDG) in 2015, several governments have prioritized environmental challenges such as air pollution, poor sanitation, and significant damage to natural resource rents (OECD 2011) and forest reserves (Pereira-Romeiro et al 2021). Governments are also focusing on green finance to solve environmental issues (Bhatnagar et al 2022b). Human health and economic well-being are jeopardized by poor environmental conditions (Tallis et al 2008).…”
Section: Introductionmentioning
confidence: 99%